The Aztec Incident: Recovery at Hart Canyon by Scott and Suzanne Ramsey, Dr. Frank Thayer, and Frank Warren - Clark, Jerome (Journal of Scientific Exploration, 2012)
One scarcely knows where to begin. Perhaps with this quote from a June 19, 1951, letter—reprinted in these pages (90–91)—written by San Francisco Chronicle editor Paul G. Smith to Variety entertainment columnist and author Frank Scully: “Frankly, I recall that when I first saw your book I thought you were merely having fun with your readers.” The book, the already scandalous Behind the Flying Saucers, which Henry Holt had issued the previous September, was a marketplace success but a disaster in every quarter that did not involve commerce. Even so prominent an early UFO proponent as Major Donald Keyhoe, the first outsider to investigate Scully’s claims of a 1948 saucer recovery near Aztec, New Mexico, rejected them as absurd and fanciful. When I read Scully’s book in junior high school, my impression—even as a naive adolescent—was the same.